Obstetric fistulae, birth outcomes, and surgical repair outcomes: a retrospective analysis of hospital-based data in Dodoma, Tanzania - Athanase Lilungulu; Balthazar Gumodoka; Mzee Nassoro; Patrice Soka; Kibusi Stephen (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
Introduction: Obstetric Fistula (OF) among pregnant women remains a widespread condition with devastating consequences and poses a significant challenge in a community as well as globally. Objective: To determine the predictors and contributing factors associated with OF and birth outcomes in women undergoing fistula repair at the Dodoma Regional Referral Hospital (DRRH). Method: This retrospective study used hospital records of women repaired over 2013 and 2014. Data were analysed using SPSS version 21 for Window (SPSS Inc., Chicago, IL, USA). Frequency tables were generated and bivariate analyses were conducted to determine the contributing factors associated with OF using chi-squared statistics. Results: Fifty two women underwent surgical repair of a fistula; 47(90.2%) were primiparous and 5(9.6%) multiparous. There were 42(80.8%) vesico-vaginal fistulae (VVF), and 10(19.2%) recto-vaginal fistulae (RVF). Of those with VVF 5 (9.6%) had been living with urine leakage for 10 years, 25 (48.1%) for 17 years, and 12 (23.1%) for 20 years; all 10 (19.2%) with RVF had been living with the defect for 10 years. No patient had been living with both vaginal and recto fistulae. Most of the fistulas were associated with prolonged difficult spontaneous vaginal delivery but two were associated with surgery: Caesarean Section and hysterectomy. Surgical repair was by the transvaginal 47(90.4%) and trans abdominal 5(9.6%) routes. Female genital mutilation (FGM) was found in all the 28 women from the Gogo tribe but only in 12 of the 24 women from other tribes. Conclusion: Timely fistula repair by experienced fistula surgeons, adhering to fastidious basic surgical principles, will improve outcomes and limit the clinical insult and distress that OF invariably causes. Keywords: obstetrics fistula, recto-vaginal fistula, vesico-vaginal fistula, surgical repair, female genital mutilation, Tanzania.